معايير الترجيح بين الضررين وتطبيقاتها المعاصرة في القضايا الأسرية والطبية - زكية بنت يوسف (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
This study is aimed at investigating the criteria for preference of one of the two harms based on Maqasid al-shari‘ah (objectives of Islamic law) and applying them to some contemporary problems concerning the family and hygiene. The study examines the definition of “al-ḍarar” (the harmful) followed by highlighting the fact that removing the harmful is the basis of al-ijtihad. Then, the concept and criteria of “al-tarjiḥ” (the preference) are explained in the light of Maqasid al-shari‘ah as elaborated by scholars of jurisprudence. Finally, the researcher applied the said criteria of preference to certain contemporary problems; three on family matters and three related to medicine. The study is based on the inductive approach in collecting relevant juristic opinions of early and contemporary scholars, including the views expressed in al-fatawa almu‘asirah (the contemporary legal opinions). As for the analysis of these different opinions on Maqasid al-shari‘ah, analytical and critical methods were also applied in establishing the strongest view on the matter concerned. The conclusion of this study comprises various findings, the most important being the determination and application of some of the criteria of preference so as to know the strongest harms between the permissibility and non-permissibility of particular problems. The legislative principles consulted in this study are al-Qur'an, al-Sunnah, al-Qawa‘id alUsuliyyah, Qawa‘id al-Maqasid and al-Qawa‘id al-Fiqhiyyah.